2019 IEEE International Ultrasonics Symposium (IUS) 2019
DOI: 10.1109/ultsym.2019.8926048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Coded Excitations for Autonomous Airborne Ultrasonic Inspection

Abstract: Unmanned Aerial Vehicles (UAVs) are receiving increasing attention for use in Non-Destructive Testing due to their ability to access areas where manual inspection is not practical. Contact-based UAV ultrasonic inspections grant the opportunity to remotely monitor the structural health of an industrial asset with enhanced internal integrity information. Ultrasonic inspection is a Non-Destructive Testing (NDT) method conventionally used in corrosion mapping. Surface contacting ultrasonic transducers provide enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This is especially relevant in light of the recent development of device prototypes capable of producing ultrasound images using only piezoelectric organic lightemitting diodes (H. Yu et al 2020) and non-contact laser ultrasound systems (X. Zhang et al 2019). Developments like these have the potential to dramatically change the ultrasound hardware paradigm.…”
Section: A Renewed Interest In Ultrasound Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…This is especially relevant in light of the recent development of device prototypes capable of producing ultrasound images using only piezoelectric organic lightemitting diodes (H. Yu et al 2020) and non-contact laser ultrasound systems (X. Zhang et al 2019). Developments like these have the potential to dramatically change the ultrasound hardware paradigm.…”
Section: A Renewed Interest In Ultrasound Hardwarementioning
confidence: 99%
“…Other synthetic aperture techniques have been widely discussed, for example inRomero-Laorden et al (2013),Jeon et al (2019), and Lim, H. H. Kim, andYoon (2021), and an earlier article byBurckhardt, Grandchamp, and Hoffmann (1974). Similarly, monostatic synthetic aperture scanners (MSASs) and monostatic fixed focus scanners (MFFSs) are two approaches worth consideration in terms of improving image quality (NickBottenus et al 2015;Ylitalo and Ermert 1994;Heuvel et al 2017; S. Nikolov, J. Jensen, and Tomov 2008).At the pulser stage, barker codes (Dayi Zhang, R Watson, Dobie, et al 2019;Xiaochun Wang et al 2021(Isla and Cegla 2017).…”
mentioning
confidence: 99%
“…Previous research demonstrated a contactbased ultrasonic inspection, using a conventional transducer with a small amount of liquid couplant and deployed by an autonomous, multi-rotor UAV. The inspection was conducted by a UAV in an indoor laboratory [4], [5].…”
Section: Introductionmentioning
confidence: 99%